Membangun Karakter Anak Usia Dini melalui Budaya Sekolah di Raudhatul Athfal Al-Azhar Citangkolo Kota Banjar - Hisam Ahyani; Nur Hidayah (Jurnal Pendidikan Raudhatul Athfal, 2021)
The importance of cultivating children's character from an early age through Bidaya school because this aims to create a young generation who is superior, intelligent, competent, quality, has responsibility and has good character in accordance with the ideals of the nation. For this reason, special methods / steps are needed in building character in early childhood in Raudhatul Athfal (RA) Al-Azhar Citangkolo, Banjar City. The research method used in this study is qualitative with 15 children as research subjects. Collecting data through interviews, and observations, and documentation. The results showed that in building children's character in Raudhatul Athfal (RA) Al-Azhar Citangkolo, Banjar City, West Java, it could be done by instilling habituation and exemplary by teachers, schools and parents at home to children including: 1) instilling honesty to children, 2) instill responsibility in children, 3) instill discipline in children, 4) instill cooperation